Fabrication and properties of a high-performance chlorine doped graphene quantum dot based photovoltaic detector - Zhao, Jianhong; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Hu, Yanbo; Yuan, Jun; Zhao, Jun; Tai, Yunjian; Cai, Yuhua (RSC advances, 2015)
Functionalized graphene quantum dot (GQD) based materials play an important role in the development of high-performance, low-cost, large-area optoelectronic devices. The progress, however, is impeded by the poor understanding of the physical mechanism for GQDs in these devices. In this paper, chlorine doped GQD (Cl-GQD) based photovoltaic photodetectors have been fabricated using a solution process, and it was found that the presence of Cl-GQDs can significantly enhance the performance of the device. The improved performance of Cl-GQD based devices has been investigated by systematically studying the structural, morphological, optical, electrical, electrochemical and photoelectrical properties. The important photovoltaic detectors parameters such as the saturation current densities ( J 0 ), barrier heights ( Φ b ), built-in potentials ( V bi ), carrier concentrations ( N ) and depletion layer widths ( W d ) have been calculated and discussed by studying the I – V and C – V characteristics under different illuminations. The frequency dependent capacitance and conductance have also been discussed. The results provide guidance for developing high-performance graphene based optoelectronic devices.